Economic Factors Affecting Corn Commodity Switching (Zea Mays) To California Papaya Commodity (Carica Papaya L.) In South Oku District - Sibuan, Sibuan; Munajat, Munajat; Sari, Fifian Permata (Nomico, 2024)
Current conditions in South Ogan Komeroing Ulu Regency, generally California papaya farming income is greater than corn farming income. This is influenced by several economic factors. Therefore, the purpose of this study was to analyze the economic factors affecting the transfer of corn commodity (zea mays) to California papaya commodity (carica papaya l.) in South OKU District. This research was conducted in South OKU District, Muaradua Subdistrict and Buay Rawan Subdistrict. Determination of the location was carried out intentionally (Purposive). The sampling method used was the multistage sampling method. Multistage sampling with a total sample size of 60 samples. The research method used in this research is the survey method. This data processing method used is the logit regression analysis method.  Based on the research that has been done, it is concluded that the economic factors that influence land conversion from corn commodity to California papaya in South OKU Regency are independent variables, namely price, farming costs, farming experience, land area and income have a significant effect on consumer decisions.